Trophic structure of cold-water coral communities revealed from the analysis of tissue isotopes and fatty acid composition. Issue 3 (16th March 2018) - van Oevelen, Dick; Duineveld, Gerard C. A.; Lavaleye, Marc S. S.; Kutti, Tina; Soetaert, Karline
ABSTRACT: The trophic structure of cold-water coral reef communities at two contrasting locations, the 800-m deep Belgica Mounds (Irish margin) and the 300-m deep Træna reefs (Norwegian Shelf), was investigated using stable isotope (δ 13 C and δ 15 N) and fatty-acid composition analysis. A broad range of specimens, with emphasis on (commercial) fish specie's, and organic matter sources were sampled using a variety of tools. Irrespective of the environmental and geographical setting, the δ 15 N values indicated that the food web encompasses roughly 1.5 to 3 trophic levels. Mobile echinoderms, i.e. sea urchins and sea stars, had highest δ 15 N values, indicative of a high trophic position in the food web. The fraction of bacterial fatty acids in reef fauna was generally low (<5%), indicating that enhanced bacterial production in the water column through seafloor seepage of nutrients ('hydraulic theory') does not form a significant energy pathway into the food web. The high fraction of algal and essential fatty acids in reef fauna and fish at both locations indicates a close coupling with surface productivity, but the transport mechanism depends on the hydrographic setting. At Træna, Calanus copepods and euphausiids form an additional link between primary production and fish, which is largely absent at Belgica Mounds. At Belgica Mounds, the reef community is primarily supported by phytodetritus, as evidenced by the high contribution of algal fatty acids in faunal tissue and seasonal chlorophyll a deposition and marine snow at the reef. The environmental setting of cold-water coral reefs influences the structure of the associated food web.